Perceived inequality in society may not motivate increased food intake in the absence of personal socioeconomic disadvantage - Bobby K. Cheon; Xenia Low; Darren Jeffian Wijaya; Albert Lee (BMC, 2023)
Abstract Background Greater levels of socioeconomic inequality across societies have been associated with higher rates of obesity and cardiometabolic disease. While these relationships could be attributed to poorer quality of health services and lower access to healthier lifestyles among disadvantaged groups in societies with greater economic inequality, this explanation does not account for those who experience relative economic security in such unequal societies (e.g., the middle and upper classes). Here, we tested whether perceptions of greater disparities between social classes in one's society (i.e., perceived societal inequality) may promote eating behaviors that risk excess energy intake. Methods In two studies, participants completed an experimental manipulation that situated them as middle class within a hypothetical society that was presented to have either large disparities in socioeconomic resources between classes (high inequality condition) or low disparities (low inequality condition), while keeping the participants' objective socioeconomic standing constant across conditions. In Study 1 (pre-registered), participants (n = 167) completed the perceived societal inequality manipulation before a computerized food portion selection task to measure desired portion sizes for a variety of foods. Study 2 (n = 154) involved a similar design as Study 1, but with inclusion of a neutral control condition (no awareness of class disparities) followed by ad libitum consumption of potato chips. Results While the high inequality condition successfully elicited perceptions of one's society as having greater socioeconomic inequalities between classes, it did not generate consistent feelings of personal socioeconomic disadvantage. Across both studies, we observed no differences between conditions in average selected portion sizes or actual energy intake. Conclusions Taken together with prior research on the effects of subjective socioeconomic disadvantage on increased energy intake, these findings suggest that perceptions of inequality in one's society may be insufficient to stimulate heightened energy intake in the absence of personal socioeconomic disadvantage or inadequacy.